(untitled) (Bangladesh Journal of Medical Science, 2011)
Background: Acute extradural haematoma (EDH) remains most common cause of mortality and disability resulting from traumatic brain injury. In the last three decades, improvements in rescue, neuromonitoring, diagnostic procedure and intensive care have led to better outcomes. The purpose of this study was to evaluate the factors influencing the outcome in patients with EDH undergoing surgery treated in a tertiary hospital in Bangladesh. Methods: In this retrospective study, 102 consecutive patients with acute EDH who underwent craniotomy were included. The study was carried out from July 2003 to December 2005. The diagnosis was made clinically and radiologically by CT scan. Patients were grouped on the basis of Glasgow Coma Scale (GCS) and operative outcomes were evaluated by Glasgow Outcome Scale (GOS) Results: More than half sampled respondents’ (57%) age were more than 20 years while rests of the patients below 20 years with male predominance (Male: Female -12:1). About 7 in 10 respondents (70.6%) were working. Similarly, majority of the respondents (79.4%) had lost more than 30 ml blood. A notable proportion of the respondents (73.5%) had good GCS score (9-15 score) during admission. Similarly majority of the respondents (70.6%) had GCS score 9-15 and 29.4% had GCS score 3-8 before surgery. Road Traffic Accident (RTA) (65%) is the most common cause of EDH followed by assault (20%) and fall from height (12%). Temporal and temporo-parietal locations were the most common site of EDH (56%). Patients with good GCS before surgery had significantly better outcome (89%) compare to those who had bad GCS (10%). Conclusion: Level of consciousness before surgery is the most important factor affecting the outcome. Hence, early diagnosis and surgical intervention is very essential. Key words: Acute Extradural Haematoma (EDH); Glasgow Coma Scale (GCS); Glasgow Outcome Scale (GOS). DOI: http://dx.doi.org/10.3329/bjms.v10i2.7806 Bangladesh Journal of Medical Science Vol.10 No.2 Apr’11 pp.112-120